2013
DOI: 10.1074/jbc.m112.415570
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Placement Influences Reactivity in Non-heme Fe(II) Halogenases and Hydroxylases

Abstract: Background: SyrB2 is a non-heme Fe(II) halogenase that reacts on tethered amino acid substrates. Results: Hydroxylation and hydrogen abstraction are less sensitive to substrate positioning at the active site than halogenation. Conclusion: Observed halogenation of native L-Thr substrate by SyrB2 can be explained by positioning effects. Significance: Our work could inform how to redesign tether-dependent enzymes toward alternative products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 55 publications
7
70
1
Order By: Relevance
“…The concept that substrate positioning is the main determinant in halogenation is also supported by additional computational and electron paramagnetic resonance spectroscopy studies. 287290 Furthermore, geometries and molecular orbitals accessed within the catalytic trajectory may play an additional role in selectivity. 291 …”
Section: Non-heme Iron-dependent Halogenasesmentioning
confidence: 99%
“…The concept that substrate positioning is the main determinant in halogenation is also supported by additional computational and electron paramagnetic resonance spectroscopy studies. 287290 Furthermore, geometries and molecular orbitals accessed within the catalytic trajectory may play an additional role in selectivity. 291 …”
Section: Non-heme Iron-dependent Halogenasesmentioning
confidence: 99%
“…19,20 Recently, it has been shown that the O 2 reactivity of the α-KG-bound halogenase SyrB2 results in a 5C trigonal bipyramidal Fe(IV)=O intermediate with the Fe–O vector perpendicular to the C–H bond of the substrate. H-atom abstraction by an Fe(IV)=O π* molecular orbital leads to an intermediate where the Fe(III)–OH moiety is oriented away from the substrate carbon radical and the halide is primed for rebound halogenation.…”
Section: Introductionmentioning
confidence: 99%
“…The halogenase shows barely detectable hydroxylase activity with its native substrate, approximately equivalent halogenase and hydroxylase activities with the L-2-aminobutyric acid adduct, and primarily hydroxylation activity toward the tethered L-norvaline at position C5 with minor halogenation activity at C4 (66). Density functional theory applied to SyBr2 with its native and non-native tethered substrates shows that the phosphopantetheine moiety of the carrier protein also has an influence on the positioning of the substrate in the active site, ultimately dictating the halogenation versus hydroxylation activity (67).…”
Section: Halogenationmentioning
confidence: 99%